2014
DOI: 10.1088/1054-660x/25/1/015804
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optical characterizations of monoclinic LaxGd1−xCa4O(BO3)3 (x = 1, 0.09, 0.13) single crystals

Abstract: The 1064 nm optimal spatial phase matching (PM) direction for LaCa 4 O(BO 3 ) 3 (LaCOB) crystals was found to be (113.5°, 43.8°) with d eff of 1.34 pm V −1 , angular acceptance of 0.9 mrad cm and walk-off angle of 14.9 mrad, and more than a 56% second-harmonic generation (SHG) conversion efficiency was realized on a sample (4 × 4 × 6 mm 3 ) cut in this direction, by using a 1064 nm Nd : YAG pico-second laser. The angular noncritical phase-matching (A-NCPM) wavelengths along the y and z axes for La x Gd 1−x COB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(57 reference statements)
0
0
0
Order By: Relevance
“…Crystals which display large first and second order hyperpolarizability are the reason for getting high nonlinear response [1][2][3][4]. Organic crystals have an eye of attraction because of their promising high nonlinear optical susceptibilities with less time of optical response and flexibility to fabricate the compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Crystals which display large first and second order hyperpolarizability are the reason for getting high nonlinear response [1][2][3][4]. Organic crystals have an eye of attraction because of their promising high nonlinear optical susceptibilities with less time of optical response and flexibility to fabricate the compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches showed that the family of RECa 4 O(BO 3 ) 3 (RECOB, RE = Y, Gd, La, Tm, Sm, and Nd) crystals were found to be melted congruently and could be grown into a large-size by the Czochralski (Cz) pulling method [14][15][16][17]. More meaningful, the substitutional solid solutions of RE1 x RE2 1−x COB (RE1 = Y, RE2 = Gd, and La) crystals were found to have compositional uniformity along the growth direction [18][19][20]. Furuya et al had found that the ratio of a/b and a/c for Gd x Y 1−x COB crystals were linear variation with the changing of chemical composition x, and their A-NCPM third-harmonic-generation (THG) wavelengths were tunable to be around 1064 nm by keeping the variable x = 0.28, in 1999 [21].…”
Section: Introductionmentioning
confidence: 99%